Effect of cultural difference on preference for popular Malaysian cuisines - Boo, Huey Chern; Kuan, Tuck Keong; Loo, Poh Theng (2009)
Monosodium glutamate, a sodium salt of glutamic acid with the unique unami taste, is a popular flavor enhancer of food. It has been demonstrated that unami has a distinct taste which is not composed of the four basic “classic” tastes. Today, the four basic types of taste and unami are the most universal sensory characteristics of food, regardless of culture. As an attempt to better understand the cultural influence on consumer food preference, this study was undertaken to examine food preferences among the three major ethnic groups in Malaysia. This research also explored the optimal level of MSG concentration in four popular local cuisines. Results showed that consumers from different cultural backgrounds or ethnic groups differ in their food preference ratings. Specifically, Chinese consumers appeared to exhibit some underlying factors that lead to difference in food preference. The relationship between MSG concentration and food preference is a curvilinear function. The results of this study suggest several important implications for academicians and industry practitioners.